Teknologi Informasi Dalam Menunjang Keefektifan dan Keefesienan Manajemen Sekolah - Setiabudi, Agung; Wati, Lilis; Karnia, Karnia (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2022)
The industrial revolution 4.0 is growing rapidly in various fields of life, one of which is the education sector. The rapid development of technology has a positive impact on every element of society. One sector that takes advantage of the development of information technology is the education sector. Educational institutions are required to be able to develop a management information system (MIS) in order to improve the quality of educational services. Currently, educational institutions have various needs in implementing and managing their organizations or institutions. Information Technology is a number of data that has been processed through data processing in order to test the level of truth and achievement in accordance with the needs of information technology in management. There are three important things that must be considered from information, namely: (1) information is the result of data processing, (2) provides meaning, (3) is useful and useful. Currently, internet-based learning, such as web-learning, e-learning or online learning (distance learning) has been widely practiced. These lessons use the internet as a medium. In addition to learning to be more flexible in terms of time, place and age, students can also access the information needed in learning freely. Seeing the development of the current era, all aspects of life cannot be separated from Information Technology (IT), especially in the world of education. Starting from the student data management system, it has now been facilitated by the existence of information technology. Through an online-based system, filling in student data from elementary schools is easy to upload and can be received directly by the Minister of Education and Culture quickly. It doesn't just stop there, now teachers are also required to utilize information technology in an effective and efficient learning process.